POLB 001, a p38 MAPK inhibitor, decreases local and systemic inflammatory responses following in vivo LPS administration in healthy volunteers: a randomised, double-blind, placebo-controlled study - de Bruin, Digna T.; Jansen, Manon A. A.; Pereira, Diana R.; van Schijndel, Lisa; Klaassen, Erica S.; Otto, Marije E.; Skillington, Jeremy; Maguire, Paula; Tremble, Liam; Bell, Alan; Maher, Laura; Mihara, Katsuhiro; et al. (Frontiers in Immunology, 2026)
Background and aimPOLB 001 is an oral p38 mitogen-activated protein kinase (MAPK) inhibitor in development for the prevention of cancer immunotherapy-induced cytokine release syndrome (CRS). It has previously been shown to be well tolerated and capable of decreasing ex vivo lipopolysaccharide (LPS)-induced tumour necrosis factor (TNF) secretion in a phase 1 first-in-human trial. This study aimed to evaluate the anti-inflammatory effects of POLB 001 following in vivo LPS administration in healthy volunteers.MethodsParticipants received POLB 001 at doses of 30, 70, or 150 mg, or placebo, twice daily for seven consecutive days and were challenged locally with intradermal (ID) LPS on day 4 and systemically with intravenous (IV) LPS on day 6. Following ID LPS administration, skin perfusion and erythema were measured, and skin suction blisters were created to collect blister fluid containing infiltrating immune cells and extracellular fluid. Following IV LPS administration, circulating cytokine levels, leukocyte counts, leukocyte p38 MAPK phosphorylation levels, and vital signs were measured.ResultsPOLB 001 was well tolerated. It reduced the ID LPS-driven immune cell attraction and cytokine responses measured in blister fluid. The suppression of immune cell recruitment was most pronounced in neutrophils (72.4%–81.5%, p = 0.0091), classical monocytes (68.4%–73.6%, p = 0.0036), CD3+ T cells (56.4%–65.9%, p = 0.0047), and myeloid dendritic cells (59%–64.4%, p = 0.0174). The suppression of cytokine responses was most pronounced for TNF (35.3%–65.1%, p = 0.0099). Overall, POLB 001 did not substantially modulate the intradermal LPS-driven increase in local erythema and perfusion. POLB 001 significantly reduced the IV LPS-driven increase in interleukin (IL)-6, IL-8, and TNF (37.7%–80.7%, all p < 0.0003), p38 MAPK phosphorylation levels in target cells (16.7%–60.9%, all p < 0.0001), and heart rate increase (4–9.3 bpm, p < 0.0001).ConclusionPOLB 001 was safe and well-tolerated. Pharmacodynamic findings confirm that POLB 001 inhibits LPS-induced local and systemic inflammation in vivo through inhibition of p38 MAPK.Clinical trial registrationhttps://onderzoekmetmensen.nl/en/trial/51741, identifier NL81214.056.22.